Incidence of pulmonary vein conduction recovery in patients without clinical recurrence after ablation of paroxysmal atrial fibrillation: Mechanistic implications - Jiang, Ru-hong; PO, Sunny S.; Tung, Roderick; Liu, Qiang; Sheng, Xia; Zhang, Zu-wen; Sun, Ya-xun; Yu, Lu; Zhang, Pei; Fu, Guo-sheng; Jiang, Chen-yang (Heart rhythm, 2014)
Pulmonary vein (PV) isolation has become the mainstay acute procedural end point for paroxysmal atrial fibrillation (AF) ablation. To examine the incidence of conduction recovery in the PVs in patients without clinical recurrence of AF after paroxysmal AF ablation. From August 2008 to March 2011, 392 patients with drug-refractory PAF underwent catheter ablation in our center, a wide area circumferential ablation approach guided with a circular mapping catheter was performed with the intended endpoint of entrance block in all PVs. 276 (70.4%) of them were free from recurrence at one year follow-up, and 32 of them were enrolled to assess the incidence of PV reconnection. Forty-three patients with clinical recurrence after ablation were analyzed for comparison. The regions of gap were mapped and characterized in all of the reconnected PVs. Among patients without recurrence, recovery of PV conduction was observed in 29 of 32 (90.6%) patients: 10/32 (31.2%) reconnection in 4 veins, 7/32 (21.9%) in 3 veins, 10/32 (31.2%) in 2 veins, and 2/32 (6.2%) in 1 vein. No anatomic propensity was seen because reconnection was evenly distributed throughout all veins (left superior pulmonary vein 21, left inferior pulmonary vein 20, right superior pulmonary vein 19, and right inferior pulmonary vein 23). When compared to patients with recurrence, no significant differences were seen in the proportion of patients with reconnection (P = 1.0) or in left atrium-PV intervals (73.4 ± 43.3 ms vs 61.9 ± 31.8 ms; P > .05). A high incidence of PV reconnection was similarly observed in patients with and without recurrence of AF, suggesting that sustained PV isolation may not be required for freedom from clinical recurrence of AF.